The Effects of Intensive Weight Reduction on Body Composition and Serum Hormones in Female Fitness Competitors - Hulmi, Juha J.; Isola, Ville; Suonpää, Marianna; Järvinen, Neea J.; Kokkonen, Marja; Wennerström, Annika; Nyman, Kai; Perola, Markus; Ahtiainen, Juha P.; Häkkinen, Keijo (Frontiers in Physiology, 2017)
Worries about the potential negative consequences of popular fat loss regimens for aesthetic purposes in normal weight females have been surfacing in the media. However, longitudinal studies investigating these kinds of diets are lacking. The purpose of the present study was to investigate the effects of a four-month fat-loss diet in normal weight females competing in fitness-sport. In total 50 participants finished the study with 27 females (27.2 ± 4.1 years) dieting for a competition and 23 (27.7 ± 3.7 years) acting as weight-stable controls. The energy deficit of the diet group was achieved by reducing carbohydrate intake and increasing aerobic exercise while maintaining a high level of protein intake and resistance training in addition to moderate fat intake. The diet led to a ~12 % decrease in body weight (P<0.001) and a ~35-50 % decrease in fat mass ((DXA, bioimpedance, skinfolds, P<0.001) whereas the control group maintained their body and fat mass (diet x group interaction P<0.001). A small decrease in lean mass (bioimpedance and skinfolds) and in vastus lateralis muscle cross-sectional area (ultrasound) were observed in diet (P<0.05), whereas other results were unaltered (DXA: lean mass, ultrasound: triceps brachii thickness). The hormonal system was altered during the diet with decreased serum concentrations of leptin, triiodothyronine (T3), testosterone (P<0.001), and estradiol (P<0.01) coinciding with an increased incidence of menstrual irregularities (P<0.05). Body weight and all hormones except T3 and testosterone returned to baseline during a 3-4 month recovery period including increased energy intake and decreased levels aerobic exercise. This study shows for the first time that most of the hormonal changes after a 35-50 % decrease in body fat in previously normal-weight females can recover within 3-4 months of increased energy intake.